The Effect of High Dose Isoflavone Supplementation on Serum Reverse T3 in Euthyroid Men With Type 2 Diabetes and Post-menopausal Women - Sathyapalan, Thozhukat; Köhrle, Josef; Rijntjes, Eddy; Rigby, Alan S.; Dargham, Soha R.; Kilpatrick, Eric S.; Atkin, Stephen L. (Frontiers in Endocrinology, 2018)
Background. The health benefits of soy are widely reported but there are queries on the effect of soy isoflavones on thyroid function and the underlying mechanism of action. Materials and Methods. We examined the effect of soy isoflavones on reverse tri-iodothyronine (or 3,3’,5’-tri-iodothyronine; rT3) in two studies comprising 400 patients: 200 men (study 1; 3 months) and 200 postmenopausal women (study 2; 6 months) who were randomized to consume 15g soy protein with 66mg of isoflavones (SPI) daily, or 15g soy protein alone without isoflavones (SP) daily. Results. SPI supplementation increased rT3 serum concentration in both men (0.41 (0.12) vs. 0.45 (0.14) nmol/L and women 0.33 (0.12) vs. 0.37 (0.09) nmol/L at 3 months compared to SP that was not seen at 6 months. Thyroid stimulating hormone (TSH) serum concentrations increased while free thyroxine (fT4) concentrations decreased with 3 months of SPI compared to SP supplementation for both men and women. rT3 correlated with TSH in both studies (p=0.03) but not with either fT3 or fT4. fT3 levels did not differ between the SPI and SP preparations. Conclusion. Soy isoflavones transiently increased rT3 levels within 3 months though reverted to baseline at 6 months. The mechanism for this would be either rT3 degrading deiodinase 1 and/or deiodinase 2 activities are transiently inhibited at 3 months, or inhibition of deiodinase 3, which generates rT3 from T4 is induced at 6 months. These changes were mirrored in the TSH concentrations, suggesting that short-term high dose isoflavone transiently impairs thyroid function in the first 3 months and may impact on general health during this period.